2021
DOI: 10.3390/foods10020454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Management and Training System on Negroamaro Wine Aroma

Abstract: This study aimed to assess the impact of two soil managements and training systems on yield and wine aroma compounds of Negroamaro variety grown in a warm climate region (southern Italy). Cover crop (CC) and soil tillage (ST) as soil management, whilst bilateral Guyot (BG) and monolateral Guyot (MG) as training systems were compared. Free and bound volatile fractions were evaluated by GC-MS. ST and CC as well as BG and MG significantly affected yield parameters. In particular, yield was higher in ST and BG tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The training system is an essential factor to manage the canopy, which plays a fundamental role in light energy capture via photosynthesis, as it regulates transpiration and microclimate of ripening grapes, thus affecting yield and quality [ 21 ]. So, we measured the temperature, humidity, Pn, and Tr of the canopy after sampling.…”
Section: Resultsmentioning
confidence: 99%
“…The training system is an essential factor to manage the canopy, which plays a fundamental role in light energy capture via photosynthesis, as it regulates transpiration and microclimate of ripening grapes, thus affecting yield and quality [ 21 ]. So, we measured the temperature, humidity, Pn, and Tr of the canopy after sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Free and glycoside bound volatiles of grapes and free volatiles of wines were extracted by solid phase extraction as described by Toci et al 20 . Then, volatile compounds of extracts were analyzed using an Agilent 6890 gas chromatograph equipped with an Agilent 5975 mass spectrometer (Agilent, Santa Clara, CA, USA) and a DB‐Wax (60 m, 0.25 mm inner diameter, 0.5 mm film thickness) capillary column (J&W Scientific, Folsom, CA, USA) at the operative conditions reported previously 6 . For each replicate, volatile composition was analyzed in triplicate and the results were expressed as mg kg −1 and mg L −1 for grapes and wines, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In Tendone, all clusters result in being shaded by a ‘leaf roof’, which prevents excessive exposure of fruit to sunlight. It is reported that sun exposure of clusters is correlated with a series of concomitant aspects, such as an increase in berry temperature, lower titratable acidity and lower berry anthocyanin concentration as a result of their synthesis inhibition or degradation 5,6 . All of these aspects can be optimized in warm sites by reducing berry temperature with moderate or reduced fruit exposure 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Douro region, for the varieties Touriga Nacional and Touriga Franca, the influence of two systems on the composition of terpenes, norisoprenoids, and their precursors was evaluated, and it was shown that the double-cordon LYS 2/3 system produced grapes and Porto wines with higher contents of terpenes and norisoprenoid glycosylated fractions compared with vertical shoot positioning (VSP) [ 10 ]. In southern Italy, the interactions between soil management and training systems (bilateral and monolateral Guyot) were shown to be related significantly to aromatic compounds in Negroamaro wine [ 11 ] (and other studies). The most widely applied systems in Brazil are lyre (Y or V), VSP, GDC, and pergola systems.…”
Section: Introductionmentioning
confidence: 99%